BRIDGING AND NAVIGATING THE SUSTAINABLE FINANCIAL SECTOR: STRATEGIC ROLE OF FINANCIAL SECTOR LEGAL CONSULTANT - Wahyu Baskara, Agustinus Prajaka (Jurnal Paradigma Hukum Pembangunan, 2025)
There has been significant structural and regulatory transformation in the financial services sector in the last decade. The need to integrate sustainable financial sector, digitalization, and consumer protection places financial sector legal consultant in a strategic position that cannot be underestimated. Their function is not only as legal advisors, but also as compliance enablers, risk analysts, and strategic partners in the legal aspects of the business. The metamorphosis from a capital market legal consultant to a financial sector legal consultant brings profound consequences to the expansion of skill scope, adjustment of competencies, as well as increased ethical and professional responsibilities. This paper raises two issues of how can financial sector legal consultants bridge and navigate in a sustainable financial sector and how to optimize the strategic role of financial sector legal consultants? The research method of this paper is normative juridical, which examines the applicable provisions relating to the roles and responsibilities of financial sector legal consultants, mastery and sharpening of competencies that must be possessed. The data obtained from the research is analyzed qualitatively. The research results show that optimizing the strategic role of financial sector legal consultants is carried out with an agile and adaptive attitude to all dynamic changes in the financial services sector, responsive to client needs manifested in the ability to bridge all stakeholders in the financial services sector ecosystem. Financial sector legal consultants can provide proper navigation in the dynamic financial sector, especially in corporate activities and business transactions with a deep and thorough understanding of the ever-changing regulations, compliance with professional ethics, and always open to global trends and digital transformation.